2012
DOI: 10.1111/jfpp.12015
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Cooking of Maize/Spirulina Mixture: Factors Affecting Expanded Product Characteristics and Sensory Quality

Abstract: The physical properties and sensory attributes of an extruded product are generally influenced by a large number of process and ingredient variables. Expansion is the most important physical property of the snack food. The effects of spirulina powder (SP) addition to maize flour (MF) on the physico‐chemical and sensory quality of extrudates were investigated. Addition of SP (7.5%) in the MF blend increased the carotenoids, protein and zinc contents and produced crisp to hard‐textured extruded products. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 34 publications
(53 reference statements)
9
39
1
9
Order By: Relevance
“…This effect is due to the fact that higher moisture content decreases the shear of the plasticized mass inside the extruder, reducing the gelatinized starch and prevent the growth of air bubbles of the snacks (Stojceska et al, 2009;Sumargo et al, 2016). The hardness of the snacks ranged from 14.1 to 32.8 N. Similar results (16.2 to 43.4 N) were reported by Joshi et al (2014) on corn extrudates added with microalga.…”
Section: Hardnesssupporting
confidence: 76%
See 2 more Smart Citations
“…This effect is due to the fact that higher moisture content decreases the shear of the plasticized mass inside the extruder, reducing the gelatinized starch and prevent the growth of air bubbles of the snacks (Stojceska et al, 2009;Sumargo et al, 2016). The hardness of the snacks ranged from 14.1 to 32.8 N. Similar results (16.2 to 43.4 N) were reported by Joshi et al (2014) on corn extrudates added with microalga.…”
Section: Hardnesssupporting
confidence: 76%
“…WAI is related to the absorption and retention of water by the constituents of the raw material, and can be used as a gelatinization index (Joshi et al, 2014). The increase in feed moisture positively influenced the WAI (p <0.01), due to the increase in content of water available.…”
Section: Water Absorption Index and Water Solubility Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…This could also be related to the generally low values for bulk density and ER, resulting in a more porous and puffed noodles with better color. These parameters have earlier been observed to impart changes in the lightness of the extrudates (Chaiyakul, Jangchud, Jangchud, Wuttijumnong, & Winger, 2008; Joshi, Bera, & Panesar, 2014). Observations drawn from the coefficient of regression model (Table 4), indicated that the positive quadratic effect of SS (X22 ) and negative quadratic interactive effects of FMC and BT ( X 1 X 3 ) significantly ( p  < 0.05) influenced the L * and b * of the cocoyam noodles.…”
Section: Resultsmentioning
confidence: 96%
“…The textural values of the cocoyam noodles ranged from 11.93 to 16.17 N. These values were observed to significantly ( p  ˂ 0.05) differ, as a function of FMC, SS and BT (Table 5). More significantly, higher temperature extrusion usually results into a product with more air cells, lighter (reduced wall thickness), and softer extrudates (Joshi et al., 2014). Coefficient of the regression models of the texture with respect to their linear, quadratic, or interaction effects did not show significant ( p  < 0.05) effect, but the influences of these process variables observed are shown on the surface plots (Figure 1l).…”
Section: Resultsmentioning
confidence: 99%